ACCESSIBILITY IN THE INFRASTRUCTURES OF THE CITY OF MAPUTO IN LIGHT OF DECREE Nº 53/2008: STUDY OF THE GYMNASIUMS OF THE KAMPFUMO MUNICIPAL DISTRICT (MAPUTO) (REMUNOM, 2025)
This study analyzed accessibility in gyms in Maputo City, focusing on compliance with Decree No. 53/2008. The study adopted a qualitative, descriptive, and cross-sectional approach, using a convenience sample of eight gyms in the KaMpfumo municipal district (Maputo City). An observation form was used as a data collection instrument. The results show that seven of the gyms are considered "poorly accessible" and one is "not accessible" according to the categorical proposal of this dissertation. No gym was considered "accessible" for wheelchair users. The results revealed numerous non-conformities, especially in the reception area and restroom facilities, making the spaces inaccessible to people with disabilities. The conclusion is that, despite the legal framework, accessibility is still neglected, requiring urgent interventions to ensure equal access to sports, given that the lack of structural adaptations, oversight, and adequate training compromises the inclusion of this social group